Grãos secos de destilaria com solúveis em dietas para tilápia-do-Nilo - Botelho, Renan de Mattos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to determine the nutritional value of corn distillery dry grain with soluble (CDDGS) produced in Brazil, as well as replacement of soybean meal protein (SM) by the CDDGS in diets for Nile tilapia. Was conducted study to evaluate the apparent digestibility coefficients (ADC) of nutrients and energy from the SM and CDDGS. ADC were determined by the indirect method (0.1% Cr2O3 as an inert indicator) based on replacement of 30% of a reference diet (26.81 DP and 3036 kcal kg- 1 DE) by test ingredients (SM and CDDGS). For the growth performance, 220 juveniles (mean weight of 32.89 ± 1.05 g) were distributed in 20 tanks (250 L). The fish were fed isocaloric and isoproteic diets containing replacement levels of 10, 30, 50 and 70% of SM protein by protein CDDGS and a control diet without replacement, formulated based on digestible values obtained in the digestibility study for the SM and CDDGS. At the end of 90 days were evaluated the performance parameters and feed utilization, intestinal morphology and determination of hematological profile. After this period, 10 fish per treatment were subjected to grading-induced stress and hematological profile was determined. Growth performance and feed utilization were not affected by treatments, as well as hematological parameters before and also after grading-induced stress, however there was a increase (P˂0.05) for villus:crypt ratio in fish fed diets containing replacement of 50 and 70% of SM protein by protein CDDGS. An increase (P˂0.05) in hematocrit and hemoglobin fish fed diet with replacement of 30% and total plasmatic protein and albumin in receiving diet with 50% replacement. It was observed leucopenia, lymphopenia and neutrophilia increase in plasma glucose concentrations for all fish after stress. The protein CDDGS can replace the SM protein up to 70% without impair growth performance and health, and improve the integrity of the ...

O presente estudo objetivou determinar o valor nutritivo dos grãos secos de destilaria com solúveis do milho (DDGSM) produzido no Brasil, assim como a substituição da proteína do farelo de soja (FS) pela do DDGSM em dietas para tilápia do Nilo. Foi conduzido estudo para avaliar os coeficientes de digestibilidade aparente (CDA) dos nutrientes e energia do FS e DDGSM. Os CDA foram determinados pelo método indireto (0,1% de Cr2O3 como indicador inerte) com base na substituição de 30% de uma dieta referência (26,81 PD e 3036 kcal kg-1 de ED) pelos ingredientes teste (FS e DDGSM). Para o estudo de desempenho produtivo, com duração de 90 dias, 220 juvenis (peso médio de 32,89 ± 1,05 g) foram distribuídos em 20 aquários (250 L) e foram alimentados com dietas isoproteicas e isocalóricas, contendo 10, 30, 50 e 70% de substituição da proteína do FS pela proteína do DDGSM e uma dieta controle sem substituição, formuladas com base nos valores digestíveis obtidos no estudo de digestibilidade para o FS e DDGSM. Após o término do ensaio de desempenho, dez peixes por tratamento foram submetidos ao estresse por classificação e em seguida determinado o perfil hematológico. As variáveis de desempenho produtivo não foram afetadas pelos tratamentos, assim como os parâmetros hematológicos antes e após estresse por classificação, no entanto houve aumento (P˂0,05) para relação altura de vilosidades:profundidade de criptas nos peixes alimentados com dietas contendo 50 e 70% de substituição da proteína do FS pela proteína do DDGSM. Houve aumento (P˂0,05) no hematócrito e hemoglobina dos peixes que receberam dieta com substituição de 30% e na proteína plasmática total e albumina nos que receberam dieta com 50% de substituição. Observou-se leucopenia, linfopenia, neutrofilia e aumento nas concentrações de glicose plasmática para todos os peixes após...
Keywords: Tilápia-do-Nilo; Peixe - Nutrição; Digestão; Peixe - Alimentação e rações; Tilápia